Designing Ontology-based Patterns for the Representation of the Time-Relevant Eligibility Criteria of Clinical Protocols - Crowe, Christopher L. (AMIA Jt Summits Transl Sci Proc, 2015)
The amount of time and money required to screen patients for clinical trial and guideline eligibility presents the need for an automated screening process to streamline clinical trial enrollment and guideline implementation. This paper introduces an ontology-based approach for defining a set of patterns that can be used to represent various types of time-relevant eligibility criteria that may appear in clinical protocols. With a focus only on temporal requirements, we examined the criteria of 600 protocols and extracted a set of 37 representative time-relevant eligibility criteria. 16 patterns were designed to represent these criteria. Using a test set of an additional 100 protocols, it was found that these 16 patterns could sufficiently represent 98.5% of the time-relevant criteria. After the time-relevant criteria are modeled by these patterns, it will allow the potential to (1) use natural language processing algorithms to automatically extract temporal constraints from criteria; and (2) develop computer rules and queries to automate the processing of the criteria.